Age-Related Changes in the Expression of the Circadian Clock Protein PERIOD in Drosophila Glial Cells - Long, Dani M.; Giebultowicz, Jadwiga M. (Frontiers in Physiology, 2018)
Abstract Circadian clocks consist of molecular negative feedback loops that coordinate physiological, neurological, and behavioral variables into “circa” 24-hour rhythms. Rhythms in behavioral and other circadian outputs tend to weaken during aging, as evident in progressive disruptions of sleep-wake cycles in aging organisms. However, less is known about the molecular changes in the expression of clock genes and proteins that may lead to the weakening of circadian outputs. Western blot studies have demonstrated that the expression of the core clock protein PERIOD (PER) declines in the heads of aged Drosophila melanogaster flies. This age-related decline in PER does not occur in the central pacemaker neurons but has been demonstrated so far in retinal photoreceptors. Besides photoreceptors, clock proteins are also expressed in fly glia, which play important roles in neuronal homeostasis and are further categorized into subtypes based on morphology and function. While previous studies of mammalian glial cells have demonstrated the presence of functional clocks in astrocytes and microglia, it is not known which glial cell types in Drosophila express clock proteins and how their expression may change in aged individuals. Here, we conducted immunocytochemistry experiments to identify which glial subtypes express PER protein suggestive of functional circadian clocks. Glial cell subtypes that showed night-time accumulation and day-time absence in PER consistent with oscillations reported in the pacemaker neurons were selected to compare the level of PER protein between young and old flies. Our data demonstrate that some glial subtypes show rhythmic PER expression and the relative PER levels become dampened with advanced age. Identification of glial cell types that display age-related dampening of PER levels may help to understand the cellular changes that contribute to the loss of homeostasis in the aging brain.